(untitled) (Andamios, Revista de Investigación Social, 2026)
The article presents an analysis of the literacy of the contents provided by the Truth Commission. To this end, a descriptive, post-qualitative approach is developed based on an open coding matrix that allows for the discrimination of formats, content classification, and recognition of the resource’s interactivity for working on the memory of the conflict. As a result, it is established that the presentation of content and narratives allows citizens to decide the option of information to access, enabling interactivity and the construction of a prosumer role. To deepen the analysis, these results are compared with other Truth Commissions in Latin America. Transmediality enables a two-way approach to the events of the armed conflict so that they do not depend exclusively on the decision of the sender, but rather, citizens themselves interact and give meaning to the information for the construction of the collective memory of the armed conflict.